The concept of household's wellbeing: a survey of literature / Siti Nurul Akma Ahmad, Siti Mariam Ali and Mohamed Saladin Abdul Rasool - Ahmad, Siti Nurul Akma; Ali, Siti Mariam; Abdul Rasool, Mohamed Saladin (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
In the modernized world, wellbeing is defined in a variety of ways, one of which is as a reflection status of comfort for mankind. Even though the topic of wellbeing has received much attention, no consensus on a definition has been reached. As a result, the concept of wellbeing can be expanded to include an overview of household's wellbeing. Having greater insight into wellbeing of households would yield useful information to the understanding of progress and welfare of the households as well as their health status. Malaysia and other developing countries should set efforts in enhancing the wellbeing of households by conducting robust research on the wellbeing. Equally important, the wellbeing study is expected to provide a recommendation for responsible authorities, employer, and organization to put extra concerns on improving wellbeing of households as it will be the main contribution for the organization as well as the country success. This paper reviews manifold economic and noneconomic factors that are relevant to the concept of wellbeing. The objective of the paper is to present an overview of the wellbeing of households and its definition from a conventional perspective. This conceptual paper outlines the philosophy and understanding of wellbeing of households.